The influence of digital communication technology on university branding: an understanding of open and distance learning (ODL) from students’ perspectives - Sharipudin, Mohamad-Noor Salehhuddin; Rejab, Mawarny Md; Tugiman, Nursafwah; Indiyati, Diyah; Andriani, Astri Dwi (Penerbit Universiti Kebangsaan Malaysia, 2024)
Open and distance learning (ODL) refers to flexible educational opportunities regarding access and various knowledge acquisition methods. In the era of digital communication technologies, ODL offers flexible, self-directed learning techniques and comprehensive and engaging learning content. Most students at the Professional and Continuing Education (PACE) Universiti Utara Malaysia are working adults, meaning students would have to balance their employment and studies. It is a competitive industry, with each institution endeavouring to provide exceptional services to its stakeholders. The objectives of our study are 1) to understand students’ perceptions of PACE, particularly in ODL, and 2) to explore the motivation for students’ value co-creation, particularly in ODL. This study employed a qualitative method approach, namely, focus group discussions. The informants were current students from various learning centres (e.g., UUM Sintok, KL, JB, etc.). Our findings discovered four main themes for the perception of ODL students: communication engagement, service-dominant mindset, student experience, and knowledge sharing. Meanwhile, the motivation for students’ value co-creation in ODL is mainly because of attitude, active participants, facilities, satisfaction, brand loyalty and brand image. Our study provides some insights into value co-creation and how to position PACE's reputation in the minds of its stakeholders. As such, our findings were significant for PACE to communicate its corporate branding, and students may be more inclined to study at the university. Keywords: Open and Distance Learning (ODL), digital communication technology, university branding, distant learning students, Malaysia.